KEUTUHAN DAN KEPADUAN PARAGRAF TULISAN MAHASISWA PROGRAM STUDI PSIKOLOGI FKIK UNIVERSITAS JAMBI - Herman Budiyono (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2014)
This research description aim to unity and coherence paragraph artcle Studies Programme Psychology, Faculty of Medical and Health of Science, University of Jambi. Jambi. This research applies quantitative descriptive method. Population of All these research of student article paragraph, that is 45 paragraphs. From population is taken 50% at random as the sample, gotten 22 paragraphs. Research data is analysed quantitatively, the step: looks for frequency distribution by value